CpG Oligodeoxynucleotides Improve the Survival of Pregnant and Fetal Mice following Listeria monocytogenes Infection - Ito, Shu-ichi (American Society for Microbiology (ASM), 2004)
Listeria infection during pregnancy can cause the death of both mother and fetus. Previous studies established that immunostimulatory CpG oligodeoxynucleotides (ODN) increase the resistance of healthy adult mice to many infectious pathogens, including Listeria monocytogenes. This study examines whether the innate immune response elicited by CpG ODN can reduce the susceptibility of pregnant mice to lethal listeria challenge. The results indicate that CpG ODN treatment significantly improves maternal survival and reduces pathogen transmission to offspring. CpG ODN administered during pregnancy did not induce abortion, birth defects, or reduce the size or health of litters. These findings suggest that CpG ODN may provide a safe and effective means of improving the health of mothers and fetuses during pregnancy.